RETRACTED: World experience analysis in the design of sorting stations - Dulobov Doston; Saidivaliev Shukhrat; Abdullaev Rustam; Kamilov Khasan (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001